Remarcable Models of Potential Theory. (2016) - Mărginean, Diana
Abstract: In the following we present kernels on most countable sets together adjoint kernels associated, determinated by a remarcable measure, the Green function, kernels on ordered sets specially on natural numbers set N∗.